The impact of coaches’ empowering leadership on rowing athletes’ effort: the role of goals’ difficulty - Tavares, S. M.; Rodrigues, C.; van Knippenberg, D. (18th European Congress of Work and Organizational Psychology: “Enabling Change Through Work and Organizational Psychology: Opportunities and Challenges for Research and Practice”., 2017)
Purpose: This study aimed to investigate the impact of coaches’ empowering leadership on rowing athlete’s effort. The perceived difficulty of the goal set by the rowing athlete for that day’s training session was tested as a boundary condition for that effect. Using leadership empowering literature and goal setting theory, we propose that empowering leadership and goals’ difficulty interact in the prediction of athlete’s effort. Design/Methodology: To test this model we collected data from 71 rowing athletes in 2 moments: before and after the exercise session. We also collected objective data on athletes’ physical effort during the exercise session. Results: Results showed that the effect of coach’s empowering leadership on athlete’s effort depended on their perceptions of the level of difficulty of the goals set for that training session. Empowering leadership was positively related to the effort displayed by the athlete only when athletes considered the goals they had for that training session were low in difficulty. When athletes considered that their goals were very difficult, their coach’s level of empowering leadership was not a predictor of their effort. Limitations: Although effort was objectively measured, data on goals’ difficulty and perceived coach empowering leadership were self-reported. Research/Practical Implications:Our results suggest that empowering the athlete is only beneficial for his effort when goals are less difficult. Originality/Value:This paper brings together the literature on empowering leadership and goal setting. Additionally, it studies these interactive effects in rowing athletes, a population that has not been studied.